Food for thought: Exploring how people think and talk about food online. (1st April 2018) - Blackburn, Kate G.; Yilmaz, Gamze; Boyd, Ryan L.
Abstract: This exploratory study examined the ways in which people communicate about food online by analyzing food-related conversations on Reddit, a social news networking site. The Meaning Extraction Helper (MEH) was used to analyze 2 corpora and define central themes related to online food talk. In light of these themes, the researchers discuss socio-cultural components shaping the food conversations in our society in general as well as healthy versus unhealthy communities, and provided specific directions for future empirical research.